2015
DOI: 10.1186/s40816-015-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapy in acute bronchitis: what is the evidence?

Abstract: Background: Acute bronchitis, frequently emerging with the common cold is one of the most frequent causes of primary care consultations. It is a self-limiting disease which poses both high symptom burden to individuals and high financial burden to society. It is largely a viral disease (~50 % rhinovirus infection), but no causal (antiviral) treatment exists. Antibiotics, mucoactive agents, antihistamines, antitussives, decongestants are most often used but without evidence from randomized controlled trials (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
3
0
5
Order By: Relevance
“…The combinations are approved medicinal products in several countries and are recommended by the German guidelines for the treatment of acute cough 1 . In preclinical in vitro and in vivo studies anti-inflammatory characteristics and normalizing effects regarding mucus viscosity have also been shown [11][12][13][14] . A systematic review and metaanalysis confirmed that ivy-, primrose-or thyme-based remedies reduce both frequency and severity of acute cough 15 .…”
Section: Introductionmentioning
confidence: 95%
“…The combinations are approved medicinal products in several countries and are recommended by the German guidelines for the treatment of acute cough 1 . In preclinical in vitro and in vivo studies anti-inflammatory characteristics and normalizing effects regarding mucus viscosity have also been shown [11][12][13][14] . A systematic review and metaanalysis confirmed that ivy-, primrose-or thyme-based remedies reduce both frequency and severity of acute cough 15 .…”
Section: Introductionmentioning
confidence: 95%
“…Die Tatsache, dass der Erkältungshusten auch ohne Therapie spontan abklingt, soll nicht bedeuten, dass die häufig erheblichen Symptome und der Leidensdruck nicht behandelt werden sollen. In den letzten Jahren wurde für mehrere pflanzliche Präparate
Pflanzliches Präparat
, für Ambroxol
Ambroxol
und für Dextromethorphan
Dextromethorphan
eine Überlegenheit gegenüber Plazebo für den akuten Husten im Rahmen viraler Infekte gezeigt [ 3 , 4 ].…”
Section: Klassifizierung Des Hustensunclassified
“…Häufigste Ursache des akuten (bis zu 3 Wochen Dauer) oder subakuten (3)(4)(5)(6)(7)(8) Hustens ist ein viraler Infekt, der bei ansonsten gesunden Personen meist spontan abklingt. Einige pflanzliche Kombinationspräparate, Ambroxol und das Antitussivum Dextromethorphan erleichtern den Husten und verkürzen dessen Dauer.…”
unclassified
“…Nur bei Vorhandensein von Alarmzeichen ("red flags") -Dyspnoe, Hämoptoe, hohes Fieber, multimorbide, immunsupprimierte und ältere Patientensind weiterführende Untersuchungen erforderlich. In den letzten Jahren konnte für mehrere pflanzliche Präparate und für Dextrometorphan eine Wirksamkeit gegenüber Placebo für den akuten Husten im Rahmen von Erkältungsinfekten gezeigt werden [3,4]. Die Initiative "Klug entscheiden" der Deutschen Gesellschaft für Innere Medizin (DGIM) rät für den Regelfall dringend von einer antibiotischen Behandlung der akuten Bronchitis ab [5].…”
Section: Akuter Und Subakuter Hustenunclassified